SCOLIOSIS IN ADULTS AND THE POSSIBILITY OF ITS CORRECTION BY POST-ISOMETRIC RELAXATION - Yermolaieva, A.V.; Lukovskaya, O.L.; Prysiazhniuk, O.A.; Gagara, V.F. (World of Medicine and Biology, 2021)
Negative factors contribute to the progression of scoliosis in adults and complicate its treatment, despite the fact that the disease usually stops developing after puberty. Therefore, it is very important to use physical therapy methods that stabilize the spine and normalize muscle tone. In order to increase the effectiveness of physical rehabilitation of adults with scoliosis, the use of post-isometric relaxation in complex physical therapy was studied. Using pain assessment methods; functional testing of the cardiovascular and respiratory systems were examined 20 patients with scoliosis, which formed the main and control groups of 10 people. It was found that the inclusion of post-isometric relaxation in physical therapy of patients of the main group had a more statistically significant positive effect on pain intensity, static endurance of back and abdominal muscles, the functional state of the cardiovascular and respiratory systems, increased well-being, activity and mood. The obtained results give grounds to recommend the inclusion of this technique in rehabilitation programs aimed at the correction and stabilization of frontal spinal deformity in this group of patients.
Keywords: spine deformation; correction and stabilization of the spine; physical therapy; soft hand techniques; quality of life; static endurance of muscles